Critical analysis of the viability of Islamic banking system in Nigeria (a case study of Lagos state) - Mydin Meera, Ahamed Kameel (s.n, 2012)
The Nigerian Banking and other Financial Institution Decree (BOFID No.25) of 1991 has been amended to permit banking transaction based on Profit and Loss Sharing (PLS) arrangement, but yet there is no single Islamic Bank in Nigeria. This study was conducted to critically analyze the viability of Islamic banking system in Nigeria taking Lagos State as a case study. In making the study, dimensions of Viability that includes Market, Economic, Financial, Business, Political and social viability and their components such as interest, desire, awareness, attitude, perception, preference, acceptance, business, social and political inclination were investigated using three sets of questionnaires that were directed to five group of respondents namely, potential individual customers, business entities, government agencies professionals in the banking sector and regulators of the Nigeria banking industry.